UJI EFEKTIVITAS EKSTRAK DAUN CENGKEH (Syzygium aromaticum) PADA NYAMUK Aedes aegypti SEBAGAI ANTI NYAMUK RAPELAN - sultanaulya muhammad; Sri Aprilianti Idris; Eko Prawibowo (Jurnal Analis Kesehatan Kendari, 2022)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. The number of dengue fever patients reported was 3,444 cases in 2016. The use of irrational chemical insecticides has caused adverse effects on the environment, such as the emergence of resistant vectors or pests against these insecticides. Seeing this, it is necessary to make an effort to get alternative insecticides, namely by using the wrong natural insecticides, namely with clove leaves (Syzygium aromaticum). This study aims to determine the effectiveness of clove leaf extract (Syzygium aromaticum) on the Aedes aegypti mosquito as a mosquito repellent anti-mosquito and the most effective concentration of test extract. The type of research used is experiment. The population in this study were clove leaves (Syzygium aromaticum), the sample in this study was 231.81 grams of clove leaf extract (Syzygium aromaticum), using maceration method. The results of this study obtained an average percentage of mosquitoes that landed using the test material, namely clove leaf extract (Syzygium aromaticum) with a concentration of 4%, namely 70%, 8% concentration of 40%, 16% concentration of 30%, and control test material ( X-Spray) is 0% and the most effective concentration of clove leaf extract (Syzygium aromaticum) is 16% concentration. Keywords : Aegypti Mosquito, Clove Leaf, Extract